Development of logistics performance measurement with process-based approach : Case study in the EV battery industry - Toivanen, Roosa (My University, 2023)
Logistics performance is a significant driver of competitiveness for manufacturing companies operating in global supply chains. Even though performance measurement is generally accepted to be essential for efficient management and improvement of performance, the performance measurement models presented in the literature have not been able to fully address the many issues that practitioners have with the development of performance measurement. Additionally, there is not yet a complete understanding of how contextual factors impact the development of performance measurement. Contract manufacturing in the automotive industry provides a niche to assess how the contextual factors impact the development of logistics performance measurement. This study has been conducted as a commissioned study by a Finnish manufacturing company operating in the electric vehicles (EV) battery industry. The purpose of this study is to establish a logistics performance measurement framework suitable for the context of contract manufacturing in the electric vehicles industry. The framework should utilise process-based approach, and it should fit the purpose of enhancing logistics management on strategic and operational levels. The study aims to provide managerial contribution to the practical business issue of the case company and to the research gaps identified in the academic literature by compiling a proposal of a performance measurement framework with balanced performance measures along the logistics processes. This framework is supported with management processes that enable the realisation of performance measurement in the context of the case company. The research approach of this study is qualitative and constructive. Semi-structured interviews were conducted in the case company with participants from the logistics department and management. The theoretical framework constructed based on the literature review was utilised to analyse the interview material. As the main managerial implication of this study, a performance measurement framework is presented to provide a solution to the practical problem of the case company. In accordance with the process-based approach, selected and developed performance measures are illustrated along the key process description. The performance measures are balanced based on several dimensions and their hierarchical level is considered. The performance measurement framework is accompanied with the definition of responsibilities, and reporting and reviewing structure that supports the use of performance measurement on a continuous basis in daily operations and strategic management. This study fills in the gap in logistics performance measurement literature by presenting a description of how the contextual factors in contract manufacturing in the automotive industry can be considered in the development of logistics performance measurement. Elements from different approaches and methods suggested in the literature are synthesised and used to form a performance measurement framework that suits the context of the case company. The study provides further validation for the use of specific logistics performance measures and process-based approach in practice.

Logistiikan suorituskyky on merkittävä kilpailukyvyn ajuri globaaleissa toimitusketjuissa toimiville valmistavan teollisuudenalan yrityksille. Vaikka suorituskyvyn mittaaminen tunnistetaan tehokkaan johtamisen ja suorituskyvyn kehittämisen keskeiseksi tekijäksi, kirjallisuudessa esitetyt suorituskyvyn mittaamisen mallit eivät ole kyenneet täysin vastaamaan niihin moniin ongelmiin, joita käytännössä kohdataan, kun aloitetaan kehittämään suorituskyvyn mittaamista. Lisäksi täydellistä ymmärrystä kontekstiin liittyvien tekijöiden vaikutuksesta suorituskyvyn mittaamisen kehittämiseen ei ole vielä muodostettu. Autoteollisuuden sopimusvalmistus tarjoaa markkinaraon arvioida, miten kontekstuaaliset tekijät vaikuttavat logistiikan suorituskyvyn mittaamisen kehittämiseen. Tämä tutkimus on tehty toimeksiantona sähköisen liikenteen akkuteollisuudessa toimivalle suomalaiselle valmistavan teollisuudenalan yritykselle. Tämän tutkimuksen tarkoitus on luoda logistiikan suorituskyvyn mittaristo, joka soveltuu sähköisen liikenteen sopimusvalmistuksen kontekstiin. Kehyksen tulee hyödyntää prosessilähtöistä lähestymistapaa ja sen tulee tukea logistiikan strategisen ja operatiivisen hallinnan kehittämistä. Tutkimus pyrkii luomaan ratkaisun tapausyrityksen käytännön liiketoimintaongelmaan sekä täyttämään kirjallisuudessa havaittuja tutkimusaukkoja kokoamalla ehdotuksen suorituskyvyn mittaamisen prosessipohjaisesta mittaristosta tasapainotetuilla mittareilla. Mittaristoa tukevat johtamisprosessit, jotka mahdollistavat suorituskyvyn mittaamisen toteuttamisen tapausyrityksen kontekstissa. Tässä tutkimuksessa on käytetty kvalitatiivista ja konstruktiivista tutkimusotetta. Aineisto kerättiin tapausyrityksessä puolistrukturoiduilla haastatteluilla, joihin osallistui logistiikkaosaston ja johdon edustajia. Haastatteluaineiston analysoinnissa hyödynnettiin kirjallisuuskatsauksen perusteella muodostettua teoreettista viitekehystä. Tutkimuksen pääasiallisena käytännön kontribuutiona esitetään suorituskyvyn mittaristo, joka tarjoaa ratkaisun tapausyrityksen käytännön ongelmaan. Prosessilähtöisen lähestymistavan mukaisesti valitut ja kehitetyt mittarit on kuvattu logistiikan keskeisten prosessien yhteydessä. Mittarit on tasapainotettu useiden ulottuvuuksien perusteella ja lisäksi on huomioitu niiden hierarkkinen taso. Suoritusmittauksen viitekehykseen liittyy vastuiden määrittely sekä raportointi- ja arviointirakenne, joka tukee suorituskyvyn mittaamisen jatkuvaa käyttöä päivittäisessä toiminnassa ja strategisessa johtamisessa. Tutkimus täyttää logistiikan suorituskyvyn mittaamista käsittelevässä kirjallisuudessa havaittuja aukkoja esittämällä kuvauksen siitä, kuinka autoteollisuuden sopimusvalmistukseen liittyvät kontekstuaaliset tekijät voidaan huomioida logistiikan suorituskyvyn mittaamisen kehittämisessä. Tutkimus tarjoaa synteesin eri lähestymistavoista ja menetelmistä, joita kirjallisuudessa on esitetty, ja muodostaa niistä tapausyrityksen kontekstiin sopivan suorituskyvyn mittariston. Tutkimus vahvistaa entisestään tiettyjen logististen suorituskyvyn mittareiden ja prosessipohjaisen lähestymistavan relevanttiuden käytännössä.
Keywords: logistics performance measurement, contract manufacturing, automotive industry, performance measure